Factors associated with health decision-making autonomy on own healthcare among Tanzanian women: A 2022–2023 demographic health survey study - Tausi Seleman Haruna; Henry Ofori Duah; Rebecca Lee (PLoS ONE, 2025)
Background Women’s health decision-making autonomy is fundamental for the health and well-being of women and their children. It empowers women to make health decisions and exercise their rights and choices surrounding their health. Like most parts of Africa, women’s autonomy in Tanzania remains contentious, with an estimated 19% prevalence of health decision-making autonomy in 2015. Given the impact of women’s health decision-making autonomy on women’s health outcomes and the fact that women’s health decision-making autonomy is an ongoing process affected by advancements in technology, economic growth, and social and cultural shifts, understanding the sociodemographic correlates of women’s autonomy is imperative. Objective To examine the factors associated with health decision-making autonomy on their own health among Tanzanian women aged 15–49. Methods A non-experimental cross-sectional study using secondary data from the current Tanzania Demographic and Health Survey and Malaria Indicator Survey (TDHS-MIS) 2022–2023. The R statistical programming language was used to run the analysis. Chi-square and Ordinal Logistic Regression were fitted to identify the sociodemographic characteristics associated with women’s health decision-making autonomy on their own health. The odds ratio with its 95% confidence interval was used to determine the significance level at p-value <0.05. All estimates were adjusted for sample design (sample weight, strata, and sampling units). Results A total of 9,249 women were included in the analysis. A large proportion (20%) of women aged 25–29. Only 1,908 (21%) of women had complete autonomy, 4,933 (53%) had joint autonomy, and 2,408 (26%) had no autonomy. Women aged 40–44 years (AOR = 2.15; 95% CI: 1.70, 2.71), a higher education level (AOR = 2.07; 95% CI: 1.39, 3.08), richest household wealth index (AOR = 1.80; 95% CI: 1.39, 2.33), currently working (AOR = 1.61; 95% CI: 1.43, 1.83), and living in the Southwest Highlands zone (AOR = 5.86; 95% CI: 4.47, 7.67) were independently associated with higher odds of complete autonomy in their own healthcare as opposed to no autonomy. Rural residence (AOR = 0.59; 95% CI: 0.46, 0.75) was associated with decreased odds of complete autonomy compared to no autonomy. Conclusion These results show that health decision-making autonomy among Tanzanian women remains very low. Efforts to empower women through better education and means to improve their economic status are needed to increase complete health decision-making autonomy on their health. Recommendation Accelerated and concerted efforts to increase health decision-making autonomy among married women will eventually improve their health and well-being and that of society. Future implications to practice, policy, and research The findings can serve as a basis for exploratory qualitative research to further understand the process of health decision-making autonomy among Tanzanian women. Stakeholders can create focused interventions to improve women’s health decision autonomy, emphasizing education and initiatives that generate income, especially in rural regions. Policymakers are encouraged to continue creating policies that promote women’s education and economic empowerment, as these factors are linked to increased autonomy in healthcare decisions.